2014
DOI: 10.1179/1743281214y.0000000185
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory assessment of isothermal separation of V containing spinel phase from vanadium slag by centrifugal casting

Abstract: V containing spinel phase was successfully separated from vanadium slag by centrifugal casting. With the process parameters of G5900 (where normal gravity G51), t520 min and T51557 K, almost all V containing spinel phase is enriched in the concentrate, while the tailing is made up of Fe 2 SiO 4 , Fe 2 TiO 4 and Mn 2 VO 4 phases. Under the hypothesis that the vanadium and silicon exist in the slag as V 2 O 3 and SiO 2 , the mass fractions of V 2 O 3 and SiO 2 in the concentrate are 25?2 and 2?2%, while those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The morphology of the slag was studied by SEM and EDS. According to previous studies for vanadiumcontaining slags, 3,9,35,36) the white phase was made up of spinel crystals, while the dark phase was the silicate phase as shown in Fig. 1(a).…”
Section: Spinel Morphology and Mean Diametermentioning
confidence: 75%
“…The morphology of the slag was studied by SEM and EDS. According to previous studies for vanadiumcontaining slags, 3,9,35,36) the white phase was made up of spinel crystals, while the dark phase was the silicate phase as shown in Fig. 1(a).…”
Section: Spinel Morphology and Mean Diametermentioning
confidence: 75%
“…It is indicated that the separation rate of solid/liquid phases has reached the maximum level and the prolonging of separation time dose no good to the separation effect. The gravity coefficient is the crucial factor for separation effect compared to separation time [23,25]. For the liquid phase, its flow trend under super-gravity field equals to the viscous resistance when the separation limitation state is reached.…”
Section: Effect Of Separation Timementioning
confidence: 99%
“…While in this study, in order to improve the flowability of liquid intermetallic compounds and keep the aluminum matrix in solid state, the separation temperature should be kept a little lower than the melting point of aluminum. Li has used the super-gravity field to separate valuable components from metallurgical slags [23][24][25]. The separation temperature in his study was usually above 1300 • C, which called high requirement on apparatus and experiment operation.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fact that phosphorus in steelmaking slag is mostly enriched in dicalcium silicate precipitating early during solidification and its density is smaller than the residual melt, the P-concentrating phase can be separated by super gravity. In addition, super gravity technology has been successfully applied in the separation and recovery of various valuable elements from different kinds of slags, [17][18][19][20] removing of impurities from alloy melt 21,22) and preparation of functionally gradient materials. [23][24][25][26][27] Based on the characteristics above, it would be possible to separate P-concentrating phase precipitating early from steelmaking slag by super gravity.…”
Section: )mentioning
confidence: 99%